1964
DOI: 10.1002/macp.1964.020710111
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phenol and cresols on the polymerization of styrene

Abstract: The effect of phenol, o-cresol, rn-cresol, and p-cresol on the polymerization of styrene in solution and emulsion was studied.It was stated that the inhibition effect is caused by remaining oxygen in these system. I n the case of polymerization under oxygen-free conditions ( i e . vacuum), no inhibition and retardation effect was seen. The chain transfer constants, Ctr, became smaller in the order: o-cresol > p-cresol > rn-cresol > phenol. It was assumed that there exists a linear relationship between C,, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1966
1966
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…It is possible to give some explanations for the reactions. Minoura et al 15 have shown that phenol and cresols act as weak chain-transfer agents in polymerization of styrene under oxygen-free conditions. Similar tra,nsfer reactions are considered to occur in these monomers as illustrated in eq.…”
Section: 6mentioning
confidence: 99%
“…It is possible to give some explanations for the reactions. Minoura et al 15 have shown that phenol and cresols act as weak chain-transfer agents in polymerization of styrene under oxygen-free conditions. Similar tra,nsfer reactions are considered to occur in these monomers as illustrated in eq.…”
Section: 6mentioning
confidence: 99%
“…However, the mixtures containing guaiacol later returned to colorless, indicating that the quinone had been consumed, and polymerization could proceed. I n similar experiments made with cresols, Minoura et al 9 proposed that the phenols were rapidly oxidized to the quinone form, that product being the actual inhibitor.…”
Section: I1 IIImentioning
confidence: 96%
“…CH=CHa or (5) The growing radical M,. attacks either the hydroxyl group or a phenolic nucleus of the monofier molecule to terminate by abstracting a hydrogen atom.…”
Section: Yh=chzmentioning
confidence: 99%